Electrochemical Studies on Kinetics and Diffusion of Li-Ions in MnO2 Electrodes. Issue 12 (26th July 2019) - Narsimulu, Daulatabad; Ghosh, Sourav; Bhar, Madhushri; Martha, Surendra K.
Abstract : In this work, beta MnO2 nanorods synthesized by one-step microwave assisted solvothermal approach are used as conversion anodes for lithium-ion batteries. The MnO2 electrode exhibits the high initial capacity of 950 mAh g −1 (third cycle) followed by 550 mAh g −1 during the 50th cycle and 1000 mAh g −1 at the end of 200 cycles at C/20 rate. The material also exhibits good capacity at higher C rates of 1C, follows the same capacity retention pattern of C/20 rate and stable over 1000 cycles. The Trasatti procedure has been used to understand the kinetics of the gradual increase in capacity with an increase in cycle number. The increase in capacity is attributed to the enhancement in pseudo capacitive contribution to the overall charge storage from 31% to 75% during 50 th and 1000 th cycles, respectively. Impedance studies further reveal that MnO2 electrodes exhibit a faster Li-ion diffusion and less resistance with an increase in cycle number. Further, the notable electrochemical performance can be attributed to the unique one-dimensional MnO2 nanorod, which shortens the Li + diffusion length, and accommodates the strain induced by drastic volume change upon continuous cycling.